2017
DOI: 10.1002/2016jd025216
|View full text |Cite
|
Sign up to set email alerts
|

Investigating dominant characteristics of fires across the Amazon during 2005–2014 through satellite data synthesis of combustion signatures

Abstract: Estimates of fire emissions remain uncertain due to limited constraints on the variations in fire characteristics. Here we demonstrate the utility of space‐based observations of smoke constituents in addressing this limitation. We introduce a satellite‐derived smoke index (SI) as an indicator of the dominant phase of large‐scale fires. This index is calculated as the ratio of the geometric mean of observed fractional enhancements (due to fire) in carbon monoxide and aerosol optical depth to that of nitrogen di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 120 publications
(197 reference statements)
3
27
0
Order By: Relevance
“…Since NO x is more efficiently produced at high MCE, the decrease of NO x emission factors could suggest a decrease in MCE during the late fire season, although we cannot rule out the influence from the declining nitrogen content in grasses as they senesce (Mebust & Cohen, ). Tang and Arellano () also observed an overall decrease in combustion efficiency across the fire season in the Amazon basin (with more forest fires than Africa) based on multiple satellite data sets. Despite the possible agreement, the magnitudes of MCE estimated in our study still remain uncertain.…”
Section: Seasonal Variation Of Co Emission Factor Combustion Efficiementioning
confidence: 88%
“…Since NO x is more efficiently produced at high MCE, the decrease of NO x emission factors could suggest a decrease in MCE during the late fire season, although we cannot rule out the influence from the declining nitrogen content in grasses as they senesce (Mebust & Cohen, ). Tang and Arellano () also observed an overall decrease in combustion efficiency across the fire season in the Amazon basin (with more forest fires than Africa) based on multiple satellite data sets. Despite the possible agreement, the magnitudes of MCE estimated in our study still remain uncertain.…”
Section: Seasonal Variation Of Co Emission Factor Combustion Efficiementioning
confidence: 88%
“…However, the two factors tend to cancel each other (Wiedinmyer et al, ). Tang and Arellano () suggested that treatment of emission factors in FINN (as well as other biomass burning emission inventories) introduces uncertainties into the emission estimates. Monks et al () showed that CO emissions in FINN are overestimated over Siberia and Myanmar.…”
Section: Observations and Model Descriptionsmentioning
confidence: 99%
“…In Collection 6 of the MCD14ML product, FRP retrieval uses a radiance-based approach in which the 4-µm radiance of individual fire pixels and surrounding background pixels are compared [24,26]. FRP can be interpreted as a measure of biomass combustion rate, and is increasingly used by the atmospheric emissions modeling community to estimate vegetation burning emissions [27,28].…”
Section: Study Areamentioning
confidence: 99%